2021
DOI: 10.1002/pat.5294
|View full text |Cite
|
Sign up to set email alerts
|

Improving mechanical properties and fretting wear resistance of ultra‐high‐molecular‐weight‐polyethylene via incorporation of zeolitic imidazolate frameworks‐carbon nano‐fiber

Abstract: Zeolitic imidazolate frameworks (denoted as ZIF8) were combined with carbon nanofiber (denoted as CNF) by a facile liquid-phase chemical route to afford ZIF8-CNF nano-hybrid as the filler of ultra-high-molecular-weight-polyethylene (abridged as UHMWPE). The as-prepared ZIF8-CNF nano-filler was incorporated into UHMWPE matrix via hot pressing to obtain the UHMWPE-matrix composite. The effects of CNF, ZIF8, and ZIF8-CNF on the thermal stability, mechanical properties, and fretting wear behavior of UHMWPE were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…This indicates that the addition of CNF hinders the orderly arrangement of UHMEPE molecular chains and that the tubular CNF with longitudinal hindrance has poor adhesion to the UHMWPE matrix and can hardly serve as a nucleation site, which leads to the reduced crystallinity of CNF/UHMWPE composites. [31] With increasing aging time, the crystallinity of both pure UHMWPE and UHMWPE/CNF composites increased significantly. The crystallinity of aged UHMWPE/CNF composites is higher than that of pure UHMWPE.…”
Section: Dsc Measurements and Crystallinitymentioning
confidence: 93%
See 1 more Smart Citation
“…This indicates that the addition of CNF hinders the orderly arrangement of UHMEPE molecular chains and that the tubular CNF with longitudinal hindrance has poor adhesion to the UHMWPE matrix and can hardly serve as a nucleation site, which leads to the reduced crystallinity of CNF/UHMWPE composites. [31] With increasing aging time, the crystallinity of both pure UHMWPE and UHMWPE/CNF composites increased significantly. The crystallinity of aged UHMWPE/CNF composites is higher than that of pure UHMWPE.…”
Section: Dsc Measurements and Crystallinitymentioning
confidence: 93%
“…Further observation of the rough section, as in Figure 11E, shows that there is a UHMWPE matrix attached around the CNF, indicating that the fracture mechanism of the composite is the peeling of the CNF from the UHMWPE matrix and the tearing of the UHMWPE matrix. It is worth noting that carbon nanofibers were found to penetrate into the polymer matrix during tensile test fracture observation of F I G U R E 1 0 SEM images of fracture surfaces: (A)-(E) pure UHMWPE with 0, 1, 3, 5, 8 weeks aged; (F)-(J) UHMWPE/CNF with 0, 1, 3, 5, 8 weeks aged UHMWPE/CNF composites by Xin et al [31] In addition, a large number of fine cracks were present in the fractures, on which many holes with sizes close to the CNF diameter appeared. This suggests that carbon nanofibers at certain locations in the CNF/UHMWPE composites can be pulled out of the polymer matrix, thus leaving holes in the cross-section.…”
Section: Mechanical Characterizations and Microstructurementioning
confidence: 99%
“…Xin et al [ 132 ] reported that zeolitic imidazolate frameworks (ZIF8) were mixed with carbon nano fiber to act as a filler for UHMWPE by a facile liquid-phase chemical reaction. The results show that ZIF8-CNF can greatly increase UHMWPE crystallization and improve its thermal and mechanical properties.…”
Section: Methodologies For Surface Modification Of Uhmwpementioning
confidence: 99%
“…Silicate minerals such as montmorillonite (MMT), 56,153,154 kaolin, 155 and zeolite 156–158 and calcium carbonate, 159 wollastonite 160,161 are the promising fillers that greatly leads to the reinforcing effect in UHMWPE due to their outstanding mechanical properties. The silicate‐based reinforcements act as nucleating agent in UHMWPE matrix which initiate heterogeneous crystallization, thus changing the morphology of the polymer and conferring significant changes in mechanical properties.…”
Section: Noncarbonaceous Fillers Based Uhmwpe Nanocompositesmentioning
confidence: 99%